An antibiotic stewardship program in a surgical ICU of a resource-limited country: financial impact with improved clinical outcomes - Kashif Hussain; Muhammad Faisal Khan; Gul Ambreen; Syed Shamim Raza; Seema Irfan; Kiren Habib; Hasnain Zafar (Taylor & Francis Group, 2020)
Background Antibiotic resistance (ABX-R) is alarming in lower/middle-income countries (LMICs). Nonadherence to antibiotic guidelines and inappropriate prescribing are significant contributing factors to ABX-R. This study determined the clinical and economic impacts of antibiotic stewardship program (ASP) in surgical intensive care units (SICU) of LMIC. Method We conducted this pre and post-test analysis in adult SICU of Aga Khan University Hospital, Pakistan, and compared pre-ASP (September-December 2017) and post-ASP data (April-July 2018). January-March 2018 as an implementation/training phase, for designing standard operating procedures and training the team. We enrolled all the patients admitted to adult SICU and prescribed any antibiotic. ASP-team daily reviewed antibiotics prescription for its appropriateness. Through prospective-audit and feedback-mechanism changes were made and recorded. Outcome measures included antibiotic defined daily dose (DDDs)/1000 patient-days, prescription appropriateness, antibiotic duration, readmission, mortality, and cost-effectiveness. Result 123 and 125 patients were enrolled in pre-ASP and post-ASP periods. DDDs/1000 patient-days of all the antibiotics reduced in the post-ASP period, ceftriaxone, cefazolin, metronidazole, piperacillin/tazobactam, and vancomycin showed statistically significant (p < 0.01) reduction. The duration of all antibiotics use reduced significantly (p < 0.01). Length of SICU stays, mortality, and readmission reduced in the post-ASP period. ID-pharmacist interventions and source-control-documentation were observed in 62% and 50% cases respectively. Guidelines adherence improved significantly (p < 0.01). Net cost saving is 6360US$ yearly, mainly through reduced antibiotics consumption, around US$ 18,000 (PKR 2.8 million) yearly. Conclusion ASP implementation with supplemental efforts can improve the appropriateness of antibiotic prescriptions and the optimum duration of use. The approach is cost-effective mainly due to the reduced cost of antibiotics with rational use. Better source-control-documentation may further minimize the ABX-R in SICU.